Should I Stay or Should I Go? The Role of Motivational Climate and Work–Home Spillover for Turnover Intentions - Kopperud, Karoline Hofslett; Nerstad, Christina G. L.; Dysvik, Anders (Frontiers in Psychology, 2020)
Emerging trends in the workforce point to the necessity of facilitating work lives that foster constructive and balanced relationships between professional and private spheres in order to retain employees. Drawing on the conservation of resources theory, we propose that motivational climate influence turnover intention through the facilitation of work–home spillover. Specifically, we argue that employees working in a perceived mastery climate are less likely to consider voluntarily leaving their employer because of increased positive—and reduced negative—work–home spillover experiences. We further argue that employees working in a perceived performance climate are more likely to consider voluntarily leaving their employer because of reduced positive—and increased negative—work–home spillover experiences. In a cross-lagged survey of 1074 employees in a Norwegian financial-sector organization, we found that work–home spillover partly mediates the relationship between a perceived mastery climate and turnover intention. Specifically, mastery climates seem to facilitate positive—and reduce negative—spillover between the professional and private spheres, which in turn decreases employees’ turnover intention. We discuss implications for practice and future research.